Hopf-zero bifurcations of reversible vector fields - Buzzi, C. A.; Teixeira, M. A.; Yang, J. (Iop Publishing Ltd, 2001)
We study the dynamics of a class of reversible vector fields having eigenvalues (0, alphai, -alphai) around their symmetric equilibria. We give a complete list of all normal forms for such vector fields, their versal unfoldings, and the corresponding bifurcation diagrams of the codimensional-one case. We also obtain some important conclusions on the existence of homoclinic and heteroclinic orbits, invariant tori and symmetric periodic orbits.